Radiosurgery for Arteriovenous Malformations and the Impact on Headaches. Issue 5 (20th February 2017) - Bowden, Greg; Cavaleri, Jonathon; Kano, Hideyuki; Monaco, Edward; Niranjan, Ajay; Flickinger, John; Dade Lunsford, L.
Abstract : Background: Arteriovenous malformations (AVMs) can underlie many diverse neurological signs and symptoms. Headaches are a common presentation that can have a significant impact on quality of life. Objective: The authors investigated Gamma Knife ® stereotactic radiosurgery (SRS) outcomes in patients with AVMs and associated headaches. Methods: This retrospective study analyzed 102 patients with AVMs who underwent SRS between 1995 and 2013. The patient's headache symptoms led to their AVM diagnosis or developed post hemorrhage of their AVM. Information regarding headache characteristics was obtained from the patient's medical records and at follow‐up using a scripted clinical interview. The median imaging follow‐up was 61.7 months and clinical follow‐up was 89.7 months. The median treatment volume at SRS was 4.1 cm 3 and the median marginal dose was 20 Gy. Results: The actuarial AVM obliteration rate was 60% at 5 years and 78% at 10 years. Patients reported that their overall headache severity decreased by −43.6% and their headache frequency was reduced by −53.4%. Headache reduction was reported in 49.1% of patients at 1 year and 69.5% at 5 years. The median time until improvement was 6.5 months. After SRS, headache medication usage decreased in 29% of patients. Permanent adverse radiation effects after SRS occurred in 3% of patients. Until obliteration was complete, the annual risk of a hemorrhage after SRS was 0.4% per year. Conclusion: Although recall bias related to a retrospective analysis can impact outcomes, headache symptoms associated with AVMs may potentially be decreased or eliminated in a subset of patients treated with Gamma Knife radiosurgery.